Sleep quality with nurse burnout during the covid-19 pandemic in East Java - Sri Sudarsih; Windu Santoso (Universitas Muhammadiyah Semarang, 2023)
The COVID-19 pandemic is currently a major global public health emergency. Health workers on the front lines during the pandemic are exposed to high chronic stress due to the high risk of infection and long working hours. These stress factors hurt sleep quality and mental health and ultimately lead to burnout in nurses. This study aimed to determine the relationship between sleep quality and nurse burnout during the COVID-19 pandemic in East Java. The research design used is correlational analytic with a cross-sectional approach. The research sample was 180 respondents who were taken by consecutive sampling technique according to the researcher's criteria for 2 weeks. Collecting data using the MBI-HSS questionnaire to measure burnout and PSQI to measure sleep quality via a google form link. Analysis of the data in this study using SPSS for Windows version 25 using the chi-square. The results showed that most of the respondents experienced poor sleep quality as many as 166 respondents (92.4%) and respondents experienced burnout were 83 respondents (53.9%). The results of the analysis obtained a p-value of -0.170 > 0.170 which means that there is no significant relationship between sleep quality and burnout. Respondents who have poor sleep quality but do not experience burnout, one of which is due to the COVID-19 pandemic, which is starting to slant, but respondents still show alertness to the incidence of COVID-19 which is indicated by the presence of several signs of burnout experienced by respondents.